1991
DOI: 10.1128/mcb.11.4.1785
|View full text |Cite
|
Sign up to set email alerts
|

BCR first exon sequences specifically activate the BCR/ABL tyrosine kinase oncogene of Philadelphia chromosome-positive human leukemias.

Abstract: The c-abl proto-oncogene encodes a cytoplasmic tyrosine kinase which is homologous to the src gene product in its kinase domain and in the upstream kinase regulatory domains SH2 (src homology region 2) and SH3 (src homology region 3). The murine v-abl oncogene product has lost the SH3 domain as a consequence of N-terminal fusion of gag sequences. Deletion of the SH3 domain is sufficient to render the murine c-abl proto-oncogene product transforming when myristylated N-terminal membrane localization sequences a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
291
0
1

Year Published

1993
1993
2001
2001

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 379 publications
(295 citation statements)
references
References 50 publications
3
291
0
1
Order By: Relevance
“…The PLXSN vector also carries the neomycin resistance gene under the SV40 promoter. Co-transfection of the PLXSN-Gas6 construct with an ecotropic packaging construct allowed us to produce a replication-defective retrovirus (Muller et al, 1991). 293 cells were used as recipient cells and transfected by the calcium phosphate method.…”
Section: Generation Of Gas6 Producing Clonesmentioning
confidence: 99%
“…The PLXSN vector also carries the neomycin resistance gene under the SV40 promoter. Co-transfection of the PLXSN-Gas6 construct with an ecotropic packaging construct allowed us to produce a replication-defective retrovirus (Muller et al, 1991). 293 cells were used as recipient cells and transfected by the calcium phosphate method.…”
Section: Generation Of Gas6 Producing Clonesmentioning
confidence: 99%
“…A precedent for such complexity in transformation by chimeric transcription factors was demonstrated in studies of three tumor-associated fusion proteins: E2A/PBX1 derived from pre-B cell lymphoblastic leukemia, PAX3/FKHR found in alveolar rhabdomyosarcoma, and E2A/HLF found in pro-Bcell acute lymphoblastic leukemia. Mutational analyses of these fusion proteins showed that while transforma- (Lam et al, 1999;Muller et al, 1991). Transformation assays were carried out as described by May et al (1993a) with the following minor modi®cations.…”
mentioning
confidence: 99%
“…Secondly, N-terminal Bcr sequences are directly responsible for the activation of the Abl tyrosine kinase in the chimeric Bcr/Abl gene products (Muller et al, 1991;Wang, 1993, 1997). Thus, through its fusion to Abl, Bcr also contributes at a biochemical level to neoplastic transformation of white blood cells.…”
mentioning
confidence: 99%